A general approach to the creation of digital twins of mobile ropeways based on mobile transport and reloading rope units - Lagerev A.V.; Lagerev I.A. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta, 2022)
The article considers the conceptual approach and practical aspects of creating digital twins of mobile ropeways formed by two end mobile transport and reloading rope units based on self-propelled multi-axle wheeled chassis of high load capacity and cross-country ability. The approach is based on a systematic representation and analysis of the design and operating modes of a mobile ropeway. As a consequence, the digital twin is formed as a multilevel hierarchical structure. It combines information mathematical models of various functional purposes and varying degrees of mutual connectivity, which are distributed by levels depending on the degree of complexity and the possibility of their further aggregation into information mathematical models of a higher level. In relation to a typical mobile ropeway, a structural and functional analysis was carried out, on the basis of which its basic components were established, and calculated structural elements (technical devices and systems) were determined, requiring the development of the necessary individual information mathematical models. Approaches to aggregation of several individual models of computational elements connected by common characteristic quantitative parameters of modeling into group information mathematical models, and then into mode and complete information mathematical models of structural and functional components of a mobile ropeway are considered. The system approach considered in the article and the multilevel hierarchical structure of the digital twin developed on its basis are useful and effective from the point of view of ensuring the modularity of creating a digital twin, its modification for mobile ropeways of a different design, the possibility of using previously developed information mathematical models for similar computational structural elements.